Quantification of internal dosimetry in PET patients: individualized Monte Carlo vs generic phantom‐based calculations. Issue 9 (14th July 2020) - Neira, Sara; Guiu‐Souto, Jacobo; Díaz‐Botana, Pablo; Pais, Paulino; Fernández, Carlos; Pubul, Virginia; Ruibal, Álvaro; Candela‐Juan, Cristian; Gago‐Arias, Araceli; Pombar, Miguel; Pardo‐Montero, Juan
Abstract : Purpose: The purpose of this work is to calculate individualized dose distributions in patients undergoing 18 F‐FDG PET/CT studies through a methodology based on full Monte Carlo (MC) simulations and PET/CT patient images, and to compare such values with those obtained by employing nonindividualized phantom‐based methods. Methods: We developed a MC‐based methodology for individualized internal dose calculations, which relies on CT images (for organ segmentation and dose deposition), PET images (for organ segmentation and distributions of activities), and a biokinetic model (which works with information provided by PET and CT images) to obtain cumulated activities. The software vGATE version 8.1. was employed to carry out the Monte Carlo calculations. We also calculated deposited doses with nonindividualized phantom‐based methods (Cristy–Eckerman, Stabin, and ICRP‐133). Results: Median MC‐calculated dose/activity values are within 0.01–0.03 mGy/MBq for most organs, with higher doses delivered especially to the bladder wall, major vessels, and brain (medians of 0.058, 0.060, 0.066 mGy/MBq, respectively). Comparison with values obtained with nonindividualized phantom‐based methods has shown important differences in many cases (ranging from −80% to + 260%). These differences are significant ( p  < 0.05) for several organs/tissues, namely, remaining tissues, adrenals, bladder wall, bones, upper large intestine, heart, pancreas, skin, and stomach wall. Conclusions: The methodology presented in this work is a viable and useful method to calculate internal dose distributions in patients undergoing medical procedures involving radiopharmaceuticals, individually, with higher accuracy than phantom‐based methods, fulfilling the guidelines provided by the European Council directive 2013/59/Euratom.